2013
DOI: 10.1371/journal.pone.0070914
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of IRM1 Enhances Resistance to Aphids in Arabidopsis thaliana

Abstract: Aphids are insects that cause direct damage to crops by the removal of phloem sap, but more importantly they spread devastating viruses. Aphids use their sophisticated mouthpart (i.e. stylet) to feed from the phloem sieve elements of the host plant. To identify genes that affect host plant resistance to aphids, we previously screened an Arabidopsis thaliana activation tag mutant collection. In such mutants, tagged genes are overexpressed by a strong 35S enhancer adjacent to the natural promoter, resulting in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…In agreement with this, FLZ proteins were found to be interacting with regulators of hormone signaling, with development and abiotic and biotic stresses supporting their role as adaptors to mediate SnRK1 signaling (8,10). Functional analysis of FLZ genes identified their roles in the regulation of many SnRK1-regulated processes (11)(12)(13). Consistent with these studies, we recently identified that two members of Arabidopsis FLZ gene family work as negative regulators of SnRK1 signaling (14).…”
supporting
confidence: 74%
“…In agreement with this, FLZ proteins were found to be interacting with regulators of hormone signaling, with development and abiotic and biotic stresses supporting their role as adaptors to mediate SnRK1 signaling (8,10). Functional analysis of FLZ genes identified their roles in the regulation of many SnRK1-regulated processes (11)(12)(13). Consistent with these studies, we recently identified that two members of Arabidopsis FLZ gene family work as negative regulators of SnRK1 signaling (14).…”
supporting
confidence: 74%
“…For instance over-expression of Increased Resistance to Myzus persicae 1 ( IRM1 ) gene might result in mechanical barriers that reduces the population size of M . persicae in A. thaliana (Chen et al, 2013). Likewise, the aphid population size was smaller in transgenic plants, overexpression of cotton photosynthesis-related gene GhPSAK1 suggesting that GhPSAK1 might improve aphid-tolerance of the transgenic plants (Zhang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…These findings can be supported by the relevant previous studies. For example Chen et al (2013) hypothesized that over-expression of IRM1 interrupted the capability of M. persicae to reach sustained phloem sap ingestion and the tested aphids needed double the time compared to the WT. Over-expression of SKU5 SIMILAR 13 ( SKS13 ) in A. thaliana led to a reduced phloem feeding of M. persicae , which was probably due to accumulation of ROS in leaves.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of FLZ genes is highly regulated by energy status and abiotic stress (Jamsheer K and Laxmi, ). Functional analyses identified that FLZ proteins are involved in the regulation of abiotic stress, ABA‐responses and growth and development (He and Gan, ; Chen et al ., ; Hou et al ., ). The transcriptional regulation of FLZ genes by sugars and the interaction of FLZ proteins with kinase subunits of SnRK1 suggest that their role in plant growth and stress adaptation is possibly mediated through the interaction with SnRK1 signalling.…”
Section: Introductionmentioning
confidence: 99%